Aplikasi Sistem Informasi Manajemen Data Korban Bencana Berbasis Android - Marwa Sulehu; Marcelina Bota Hayon (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2021)
The information administration system of the disaster victim is still managed internally, where the victim data can only be accessed in the information center, and It is difficult to access remotely for the public. The disaster victim information system is currently still being recapitulated using office applications such as word processors. The study aimed to design and implement an information system for the Makassar City Regional Disaster Management Agency based on Mobile. The system design method used is an Android-based mobile method. So from all of them, it can be concluded that the entire management information system of the disaster victim data was successfully created and running as desired. The study results indicate that the management information system of the disaster victim data based on Android mobile can help the BPBD officers input the victim data, and the public can know the results.